Legal Implications of Health Service Denial for BPJS Patients: A Study on the Principles of Universal Health Coverage - Maria Alberta Liza Quintarti; Endah Labati Silapurna; Denny Achsanul Hak; Ady Purwoto; Bambang Supriadi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Both the patients and the service providers face serious legal ramifications when health services are denied to BPJS Kesehatan participants. Such rejection might have serious legal repercussions in the context of Universal Health Coverage (UHC), which seeks to provide inclusive and equitable access to health treatments. Using the core tenets of UHC, which uphold everyone's access to healthcare free from discrimination, this article seeks to examine the legal ramifications of BPJS patients' refusal of health services. This article examines a number of variables that contribute to service denials and the legal tools that can be employed to safeguard patients' rights within the BPJS-based healthcare system by looking at pertinent legal legislation and industry practices.